Tableau Desktop - A Step-by-Step Guide for Beginners - Batra, Anil (Packt Publishing, 2020)
Get to grips with the fundamentals of Tableau and create easy-to-understand data visualizations About This Video Get acquainted with Tableau for effective data visualization Learn how to use Tableau's drag and drop and built-in functions optimally Develop the skills you need to connect Tableau with various data sources In Detail Do you want to help your organization make effective data-driven decisions? You can do that by visualizing the data in a way that everyone in your organization understands the relationship between the data and is able to make smart marketing decisions with ease. This video course will teach you how to create effective data visualizations using Tableau with the help of interesting activities. The course begins with an introduction to Tableau, showing you how to connect to a data source in Tableau. You'll then gain a solid understanding of data visualization, before going on to develop a bar chart and a pie chart, create a text table and explore map visualization in Tableau. The course will also help you to find a suitable method for using filters in a Tableau worksheet. As you advance, you'll delve into data connections by connecting multiple tables in the same data source. Toward the end, you'll learn how to effectively use the Tableau dashboard, create stories in Tableau, and share your data with others without any hassles. By the end of this course, you'll have the knowledge you need to create data visualizations using Tableau 10 and Tableau 2019, and be ready to delve further into advanced Tableau topics.
Keywords: Electronic videos